Otimização do processo de obtenção de hidrolisado proteico de semente de abóbora moranga (cucurbita maxima) - Silva, Ana Lívia Rodrigues da (Universidade Federal do Tocantins, 2023)
Because of high protein content present in moranga (Cucurbita maxima) squash seeds they have been used with several products, another alternative that has been explored to take advantage of such protein potential is the production of protein hydrolysates from seeds. This work aims to optimize the process of obtaining the protein hydrolysates from pumpkin seed flour. Pumpkin seed flour presented high protein content in its proximate composition (32.60%), which demonstrates potential to the production of protein hydrolysates. The results showed time and temperature as decisive factors to hydrolysis reaction and it was possible to validate the methodology used since a linear model was obtained at a 5% significance level. Thus, pumpkin seed protein hydrolysate proved to be applicable to food industry due to its high percent degree of hydrolysis, which makes it an excellent food additive for hospitalized patients or people who want to gain muscle mass.